Novel Bounds for Incremental Hessian Estimation With Application to Zeroth-Order Federated Learning - Alessio Maritan; Luca Schenato; Subhrakanti Dey (IEEE Open Journal of Control Systems)
The Hessian matrix conveys important information about the curvature, spectrum and partial derivatives of a function, and is required in a variety of tasks. However, computing the exact Hessian is prohibitively expensive for high-dimensional input spaces, and is just impossible in zeroth-order optimization, where the objective function is a black-box of which only input-output pairs are known. In this work we address this relevant problem by providing a rigorous analysis of an Hessian estimator available in the literature, allowing it to be used as a provably accurate replacement of the true Hessian matrix. The Hessian estimator is randomized and incremental, and its computation requires only point function evaluations. We provide non-asymptotic convergence bounds on the estimation error and derive the minimum number of function queries needed to achieve a desired accuracy with arbitrarily high probability. In the second part of the paper we show a practical application of our results, introducing a novel optimization algorithm suitable for non-convex and black-box federated learning. The algorithm only requires clients to evaluate their local functions at certain input points, and builds a sufficiently accurate estimate of the global Hessian matrix in a distributed way. The algorithm exploits inexact cubic regularization to escape saddle points and guarantees convergence with optimal iteration complexity and high probability. Numerical results show that the proposed algorithm outperforms the existing zeroth-order federated algorithms in both convex and non-convex problems. Furthermore, we achieve similar performance to state-of-the-art algorithms for federated convex optimization that use exact gradients and Hessian matrices.